Performance enhancement of cold thermal energy storage system using nanofluid phase change materials: A review - Sidik, Nor Azwadi Che; Kean, Tung Hao; Chow, Hoong Kee; Rajaandra, Aravinthan; Saidur Rahman, *; Kaur, Jesbains * (Elsevier, 2018)
Cold thermal energy storage (CTES) plays a vital role in many industrial applications such as central air-conditioning in the large buildings, high powered electronic cooling applications, waste heat recovery, food processing, and restoring the electrical power imbalance between daytime need and night-time abundance. In addition, CTES system incorporating phase change materials (PCM) is proved as a viable option for achieving high energy efficiency by many systems. Due to the significance of this issue, many studies have been conducted on the applications of PCM in CTES system. The main aim of this article is to provide a comprehensive review, which summarizes recent research progress on PCM-CTES and an overview of numerical and experimental studies on the heat transfer performance of different base fluid of PCMs. This article also discusses several factors affecting the thermal conductivity of PCMs, such as nanoparticle enhanced PCMs, shape of encapsulated PCM materials, solid volume fraction and particle size. Observation and findings from past studies are discussed in detail. Recommendations based on research results, advantages and drawbacks of PCM-CTES are made for future research directions.